1996
DOI: 10.1159/000246381
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acrogeria Associated with Late-Onset Focal Dermal Elastosis

Abstract: We report a case of acrogeria. Biochemical analysis of patient fibroblasts demonstrated unaltered type III collagen synthesis. An RNA hybridization assay demonstrated that the levels of type I and elastin mRNAs were normal. The patient had multiple yellow papules on the neck, axilla and inguinal area which clinically and histologically resembled late-onset focal dermal elastosis. Both diseases may have some similar abnormal metabolism of connective tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Classically, it has been described that the increased elastic fibers of the lesions have a normal appearance. [2][3][4][5][6] Unlike other cases, the increased elastic dermal tissue of our patients was composed of clearly abnormal elastic fibers, which appeared thick and interlacing. In our opinion, a critical review of the histopathologic illustrations of previously reported examples of late-onset focal dermal elastosis also reveals that the increased elastic dermal tissue is composed of structurally abnormal fibers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Classically, it has been described that the increased elastic fibers of the lesions have a normal appearance. [2][3][4][5][6] Unlike other cases, the increased elastic dermal tissue of our patients was composed of clearly abnormal elastic fibers, which appeared thick and interlacing. In our opinion, a critical review of the histopathologic illustrations of previously reported examples of late-onset focal dermal elastosis also reveals that the increased elastic dermal tissue is composed of structurally abnormal fibers.…”
Section: Discussionmentioning
confidence: 93%
“…This disorder affects preferentially elderly patients, with all reported cases ranging in age from 65 to 87 years, 2-5 with the exception of a 18-year old woman who suffered a premature aging syndrome. 6 Clínically, it is characterized by 2-4 mm diameter yellowish flat-topped multiple papules that may be asymptomatic or slightly pruritic. Characteristically, the lesions are arranged in groups, and in some cases, these may coalesce, resulting in confluent plaques with a cobblestone pattern.…”
Section: Discussionmentioning
confidence: 99%
“… 9 However, the cases in younger patients differ also in other clinical features from classic presentation, e.g. association with acrogeria, 6 familiarity, 7 or acral distribution. 5 , 7 From a review of the cases reported in the literature ( Table 1 ) it appears that under the term of LOFDE have been grouped heterogeneous clinical presentations, solely on the basis of the histologic trait of increased dermal elastic tissue.…”
Section: Discussionmentioning
confidence: 97%
“…LOFDE affects preferentially patients after the sixth decade, but a few reports relate to younger patients (18 years in the case of Tajima et al, 1996; around 30 years in the two familiar cases of Camacho et al, 2012; 39 years in the case 2 of Wang et al, 2012). [6][7][8] The term "focal dermal elastosis" has been proposed as an update of the nomenclature to include also these earlier presentations. 9 However, the cases in younger patients differ also in other clinical features from classic presentation, e.g.…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%
“…The first possibility seems likely because 1) degenerative skin changes were found on the nuchae, neck, axillae, and groin, where other types of elastosis are commonly seen (18)(19)(20), and 2) collagen-aggregated tissue does not contain any vessels nor sweat glands suggesting that an acute reactive aggregation had occurred in the scar-like tissue. However, it still is possible that penicillamine has some direct effect on collagen fibers.…”
Section: Discussionmentioning
confidence: 99%